CORRELATION OF UNCERTAINTY IN ILLNESS AND SELF-CARE IN TYPE 2 DIABETES MELLITUS PATIENTS - Ghina Apriyanda Salsabila; Raden Siti Jundiah; Nur Intan Hayati Husnul Khotimah (UPT Penerbitan Universitas Jember, 2022)
Background: Diabetes is a non-communicable disease (NCD) and requires adherence to self-care to maintain health and prevent the disease from worsening. Several factors affect self-care in diabetic patients, including uncertainty in illness. Uncertainty is a major source of stress in patients with chronic diseases and also reduces patient compliance with self-care behavior. This study aims to determine the correlation between uncertainty in illness and self-care in type 2 diabetes mellitus patients at the Internal Medicine Polyclinic, Bandung City Hospital. Methods: This study aims to determine the correlation between uncertainty in illness and self-care in type 2 diabetes mellitus patients at the Internal Medicine Polyclinic, Bandung City Hospital. Result: This research results show a high level of uncertainty of 56.63%, a self-care level is good and a poor of 50%, p-value = 0.033 (α<0.05). Conclusion: There is a relationship between uncertainty in illness and self-care in type 2 diabetes mellitus patients at the Internal Medicine Polyclinic at the Bandung City Hospital. This study recommends health workers improve self-care for patients with management uncertainty for type 2 diabetes mellitus patients.